Perceived of procedural justice in selection system : a case study among the successful candidates in Universiti Malaysia Pahang (UMP) - Mas Ida, R.Arifuddin (2016)
This research carried out in Universiti Malaysia Pahang to the each department with the different position of administrative officers. The objective of this research are to examine the applicant’s perceptions towards procedural justice in the selection process and to identify the strongest category of procedural justice/fairness that affect applicant’s perception. There are three methods of analysis that are used to come out the result finding which are descriptive analysis, cronbach’s alpha and procedural justice analysis.in order to get the validity and accuracy of data that are collected, the statistical analysis of SPSS was conducted to analyze the data that have been key in before the result are being interpreted.as a result, it is found that there are several elements of the procedural justice rules/aspects that affected applicant’s perception.by going through the analysis it is also found that the strongest categorical that affected the applicant’s perception towards the procedural justice in selection system is interpersonal treatment.in the selection process the decision of the employer affected to the individuals, organizations, and society that turn affect the perception of the applicants toward the selection process. The applicants perceive to have a fair highly in term of the interpersonal treatment in selection process. Thus, procedural justice is an important aspect of reactions that applicants have to personnel selection.